Improvement of Subgrade Soils by Using Marble Dust-(Libya, Case Study) - Eltwati, Ahmed; Saleh, Fares (The International Journal of Engineering & Information Technology (IJEIT), 2020)
the practice of using waste materials to modify the properties of poor soils has become increasingly important in geotechnical engineering. In recent years, much research has been devoted to the effect of this waste material on soil properties. This study aims to address the influence of marble dust powder on the performance of subgrade. Thus, soils mixed with different percentages of marble dust were tested. The CBR test and modified proctor have been used to evaluate the performance of the soils mixed with marble dust. The statistical analysis illustrated that marble dust significantly enhanced the properties of the soils. The study concludes that an addition of 10% of marble dust to untreated (control) soils yields the most satisfactory results among other percentages of marble dust. The study recommends the use of marble dust in geotechnical construction.